ANALYSIS OF SERVICE QUALITY LIVESTOCK MARKET ON TRADERS SATISFACTION USING THE IMPORTAND PERFORMANCE ANALYSIS METHOD - Neffi Sulkaisi; Mona Amelia; Nisha Selvia; Yodi Pratama (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
The study was conducted to determine the level of interest of traders in the quality of service provided by the Palangki Livestock Market Service, Sijunjung Regency, with the performance level of service quality provided by the Palangki Livestock Market Service, Sijunjung Regency to traders in the Palangki Sijunjung Regional Livestock Market. This type of research is a quantitative descriptive research. The sample used was 72 respondents. Sampling using non-probability with incidental sampling technique. The analytical methods used include Importance and Performance Analysis, Customer Satisfaction Index. The results of the calculation of the overall Customer Satisfaction Index on the quality of service provided by the Palangki Livestock Market Service are 55 percent, indicating that the traders of the Palangki Livestock Market are